PROTECTION OF THE PATIENT AGAINST PRACTICES VIOLATING COLLECTIVE INTERESTS OF CONSUMERS AND COLLECTIVE INTERESTS OF PATIENTS - Jaszczuk, Paulina (Review of European and Comparative Law, 2018)
This article is an attempt to analyse the term “patient”, determine his basic rights, as well as draw attention to practices violating collective interests of patients. It also invokes relations of the patient as a consumer, as well as practices violating collective consumer interests. It indicates the patients’ rights and the bodies appointed to protect these rights.